SP0146 The link between inflammation and depression. (12th June 2018) - Harrison, N.
Abstract : Inflammation is increasingly implicated in the etiology of depression. Patients with idiopathic depression have been shown to express increased circulating pro-inflammatory cytokines and 30% of patients receiving chronic Interferon-alpha for the treatment of Hepatitis-C develop major depression. Recently, anti-inflammatory agents, including 'biologics' developed for rheumatoid arthritis, have shown potential efficacy for the treatment of idiopathic depression. However, the utility of these medications is highly variable emphasising the importance of identifying biomarkers that may predict treatment response. Interestingly, neuroimaging studies have recently demonstrated that increases in inflammation can rapidly alter brain function and microstructural integrity. Further, these acute changes in brain structure/function can additionally predict the later development of depressive response during sustained inflammatory challenge. For example, in patients with Hepatitis-C given Interferon-alpha over a prolonged period, acute changes in ventral striatal microstructure (observed within 4 hours of the first injection of Interferon) predict the magnitude of fatigue/motivational impairment experienced 4 weeks later while acute changes in amygdala processing of emotionally valenced stimuli predicts the magnitude of depressive symptoms. Conversely, inhibitors of Tumour Necrosis Factor (TNF) reduce amygdala reactivity to emotional stimuli, which correlate with improvement in mood. Together, these studies highlight the importance of inflammatory processes in depression and support on-going trials of anti-inflammatory agents in this common and functionally impairing disorder. Disclosure of Interest: N. Harrison Grant/research support from: Janssen, Consultant for: GSK